The male and female gonad transcriptome of the edible sea urchin, Paracentrotus lividus: Identification of sex-related and lipid biosynthesis genes - André M. Machado (Elsevier, 2022)
Paracentrotus lividus is the most abundant, geographically distributed, and desirable echinoid species in Europe. Although economically important, this species has scarce genomic resources available. Here, we produced and comprehensively characterized the male and female gonad transcriptome of P. lividus. The P. lividus transcriptome assembly has 53,865 transcripts, an N50 transcript length of 1842 bp, and an estimated gene completeness of 97.4% and 95.6% in Eukaryota and Metazoa BUSCO databases, respectively. Differential gene expression analyses yielded a total of 3371 and 3351 up-regulated genes in P. lividus male and female gonad tissues, respectively. Additionally, we analyzed and validated a catalog of transcripts pivotal in sexual development and determination (206 transcripts) as well as in biosynthesis and storage of lipids (119 transcripts) in male and female specimens. This study provides a valuable resource and will contribute to the future conservation of the P. lividus species as well as its exploitation in an aquaculture setting.